Estimation of YKL-40 levels in serum and gingival crevicular fluid in chronic periodontitis and type 2 diabetes patients among South Indian population: A clinical study - Prathush Ajit Kumar; Krishna Kripal; Kavita Chandrasekaran; Sushma Reddy Bhavanam (Wolters Kluwer Medknow Publications, 2019)
Background: YKL-40 is a novel potential inflammatory marker in relation to both acute and chronic inflammation. It is secreted by activated neutrophils and macrophages in acute or chronic inflammation. It strongly binds to chitin and heparin. There remains paucity in information regarding the quantification of YKL-40 levels in serum and gingival crevicular fluid (GCF) in patients with periodontal disease. Aim: The aim of this study was to evaluate and estimate the YKL-40 levels in serum and GCF samples collected from patients with or without periodontitis and type 2 diabetes among the South Indian population. Materials and Methods: A total of 40 patients were included who were divided into four groups based on inclusion and exclusion criteria as follows: Group A comprised ten healthy individuals, Group B comprised ten patients diagnosed with chronic periodontitis without type 2 diabetes, Group C comprised ten patients diagnosed with chronic periodontitis with type 2 diabetes, and Group D comprised ten patients diagnosed with only type 2 diabetes. Gingival Index (GI), pocket depth (PD), and clinical attachment level (CAL) were recorded at baseline. Serum and GCF samples were collected at baseline which were subjected to enzyme-linked immunosorbent assay analysis for estimation of YKL-40 levels. Results: All the clinical parameters (GI, PD, and CAL) and the concentration of YKL-40 level in serum and GCF samples were statistically significant among the groups. The amount of YKL-40 in GCF and serum was found to be highly correlated with PD of patients in all the groups. Conclusions: Within the limitations of the sample size, the present study indicates that the measurement of YKL-40 in Serum and GCF samples shows potential as a quantitative indicator of periodontal disease extent.